Polymer nanocomposite coatings - Mittal, Vikas (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This work explores the use of composite nanotechnology for thin coatings on various substrates. It compiles recent advances in nanocomposite coatings for experienced researchers and provides background information for those new to the field. The book not only explains the synthesis of bulk nanocomposite materials, but also describes their application in areas such as the automotive and packaging industries. It explains how nanocomposite coatings provide a gas barrier to the substrate foil or laminate and how the coatings are used to provide properties such as anti-scratch and anti-corrosion.'--
'Preface The main focus of this book is the coatings generated with polymer nanocomposite materials. Polymer nanocomposites have been developed continuously for the last two decades. These advancements have led to their applications in many fields like automotive, packaging, etc. Coatings are one such product that are common to many application fields. They are used to enhance the functionality of the substrate in order to gain certain performance parameters. For example, in the case of packaging, these coatings provide a gas barrier to the substrate foil or laminate. On the other hand, in the case of automobiles, they are used to provide properties like antiscratch, anticorrosion, etc. Generation of coatings has additional requirements like choice of suitable dispersion medium, processing/polymerization conditions, and tuning of the properties according to specific requirements. This may require mixing of preformed polymer matrix with the filler or the formation of polymer in situ in the presence of filler. Formation of filler in the presence of the polymer may also be achieved. These operations also need to be carried out while taking into account the interaction of the coating materials with the substrates, as the adhesion of these two components is of utmost importance in achieving optimal performance. Chapter 1 provides an overview of the state of the art in the field of silver- polysaccharide systems, with particular attention to the biomedical and food-packaging fields'--
Silver-polysaccharide nanocomposite antimicrobial coatings / Andrea Travan, Eleonora Marsich, Ivan Donati, Massimiliano Borgogan, and Sergio Paoletti -- Polymer nanocomposite coatings: effects of crosslinkers and fillers on the microstructure and gas permeation / Vikas Mittal -- Carbon nanotubes-polytetrafluoroethylene nanocomposite coatings / Natthakan Rungraeng and Soojin Jun -- Organic-inorganic hybrid coatings with enhanced scratch resistance properties obtained by the sol-gel process / Massimo Messori and Marco Sangermano -- Chitosan-magnesium aluminum silicate nanocomposite coatings / Thaned Pongjanyakul -- View from inside the surface of nanocomposite coatings / Milena Spirkova and Jiri Brus -- Properties of nanocomposite hard coatings on polycarbonate / Raghavan Subasri -- UV-cured polymer: Boehmite nanocomposite coatings / Carola Esposito Corcione and Mariaenrica Frigione -- Protective coatings based on silsesquioxane nanocomposite materials / Bogdana Simionescu, Irina-Elena Bordianu, Magdalena Aflori, Florica Doroftei, Corneliu Cotofana, and Mihaela Olaru -- POSS-containing nanocomposite polymer coatings / Yasmin Farhatnia, Aaron Tan, and Alexander M. Seifalian -- Nanocomposite PPy coatings for Al alloys corrosion protection / Kirill L. Levine -- Ultrasound-assisted synthesis and its effects on the properties of CaCO3-polymer nanocomposites / Bharat A. Bhanvase and Shirish H. Sonawane.
Includes bibliographical references and index.
Keywords: Plastic coating; Nanocomposites (Materials).; Polymeric composites